2x+3+x=x+3

Simple and best practice solution for 2x+3+x=x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3+x=x+3 equation:


Simplifying
2x + 3 + x = x + 3

Reorder the terms:
3 + 2x + x = x + 3

Combine like terms: 2x + x = 3x
3 + 3x = x + 3

Reorder the terms:
3 + 3x = 3 + x

Add '-3' to each side of the equation.
3 + -3 + 3x = 3 + -3 + x

Combine like terms: 3 + -3 = 0
0 + 3x = 3 + -3 + x
3x = 3 + -3 + x

Combine like terms: 3 + -3 = 0
3x = 0 + x
3x = x

Solving
3x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
3x + -1x = x + -1x

Combine like terms: 3x + -1x = 2x
2x = x + -1x

Combine like terms: x + -1x = 0
2x = 0

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| 18q^2-39qt-189t^2=0 | | 6x-1x=6-6 | | 2i/3i | | 2w+2(1w+283)=19 | | 5p-95p+119p-p=151 | | 3[x+5]=27 | | 8x^2+10x+25= | | 2(3a+1)=5(a-1) | | 66-2r+1=3r-5(r-2) | | F(10.5)= | | 28+x=14 | | 6=x-3/2 | | 2(p+5)-3(p-7)=43 | | (9x^7)(-8x^5)=0 | | 10(d+9)=210 | | 7x-7-5x=2 | | 40-[3c+4]=4[c+5]+c | | 40-[3c+4]=[c+5]+c | | 4m-3=6m+5 | | -7t+4=-10t-14 | | 4[m+4]=40 | | -7+4=-10+-14 | | 2x+50=110 | | 14x^4+92x-42x^2=0 | | 2x-3y+i(x-2y)=4-5i | | -4(7-5m+n)= | | 6+4b=2+5b | | -3=21m | | M+2M-2=0 | | 6(w+1)-(3-2w)=7w | | 3x2squared/12x6squared | | 9m+13=58 |

Equations solver categories